Moral is political; Notions of ideal citizenship in Lie Kim Hok's "Hikajat Khonghoetjoe" - Sutrisno, Evi (Wacana, Journal of the Humanities of Indonesia, 2017)
This paper argues that the Hikajat Khonghoetjoe (The life story of Confucius), written by Lie Kim Hok in 1897, is a medium to propose modern ideas of flexible subjectivity, cosmopolitanism, active citizenship and the concepts of good governance to the Chinese Peranakans who experienced political and racial discrimination under Dutch colonization. Using the figure of Confucius, Lie aimed to cultivate virtuous subjects who apply their faith and morality in political sphere. He intended to raise political awareness and rights among the Chinese as colonial subjects and to valorize their bargaining power with the Dutch colonial government. By introducing Confucianism, Lie proposed that the Chinese reconnect themselves with China as an alternative patronage which could subvert White supremacy. Instead of using sources in Chinese, Lie translated the biography of Confucius from the European texts. In crafting his story, Lie applied conglomerate authorship, a technique commonly practised by Malay authors. It allowed him to select, combine and appropriate the source texts. To justify that Confucius' virtue and his teaching were superb and are applicable to contemporary life, Lie borrowed and emphasized European writers' high appraisal of Confucianism, instead of using his own arguments and opinions. I call this writing technique "indirect agency".